Interactive Media Development to Improve Student Motivation - Abd. Ghofur; Ety Youhanita (Universitas Muhammadiyah Mataram, 2020)
The study aims to conduct interactive multimedia development courses learning strategies to improve student motivation learning. This research uses the R&D (research and Development) research type with the ADDIE development model. The results showed that the phase of the Interacive Multimedia Development adopted an ADDIE development model which was modified into four phases, namely analysis, design, development, and implementation. Interactive learning media testing using Google Classroom media developed with media flowcharts in line with storyboards created. The validation results of media experts are not required to revise because they meet excellent categories (92%), and good category (84%). While the results of trials in improving motivation to learn to students of University of PGRI Adi Buana Lamongan Campus average get a score of 115.46 pretes with variants of 16.56, while the test post score of 140.11 with a variant of 14.99. In addition, the results of statistical trials used using the T-Test concluded that there was an increased motivation to study learning strategy courses on students using interactive multimedia.